Identification of Glycine Receptor α3 as a Colchicine-Binding Protein - Zhou, Xikun; Wu, Mingbo; Xie, Yongmei; Li, Guo-Bo; Li, Tao; Xie, Rou; Wang, Kailun; Zhang, Yige; Zou, Chaoyu; Wu, Wenling; Wang, Qi; Wang, Xiangwei; et al. (Frontiers in Pharmacology, 2018)
Colchicine (Col) is considered a kind of highly effective alkaloid for preventing and treating acute gout attacks (flares). However, little is known about the underlying mechanism of Col in pain treatment. We have previously developed a customized virtual target identification method, termed IFPTarget, for small-molecule target identification. In this study, by using IFPTarget and ligand similarity ensemble approach (SEA), we show that the glycine receptor alpha 3 (GlyRa3), which play a key role in the processing of inflammatory pain, is a potential target of Col. Moreover, Col binds directly to the GlyRa3 as determined by the immunoprecipitation and bio-layer interferometry assays using the synthesized Col-biotin conjugate (linked Col and biotin with polyethylene glycol). These results suggest that GlyRa3 may mediate Col-induced suppression of inflammatory pain. However, whether GlyRa3 is the functional target of Col and serves as potential therapeutic target in gouty arthritis requires further investigations.